MENINGKATKAN KEMAMPUAN BERBICARA SISWA DENGAN MENGGUNAKAN METODE BERCERITA - Delfina Fadilah Harahap; Shoufi Nisma Dewi; Rahmat Huda; Paisal Khodri Siregar; Nabila Nurhaliza Ali; Salma Awae (CV. Alfa Pustaka, 2026)
This research aims to identify the improvement of students' speaking ability through the implementation of the Storytelling Method among eleventh-grade students at SMA Negeri 4 Padangsidimpuan. The study employed a mixed-methods explanatory sequential design, involving a purposive sample of seven students from class XI-8 who underwent a multi-stage screening process including placement tests and interviews. Quantitative data were collected using pre-test and post-test speaking assessments, while qualitative insights were obtained via semi-structured interviews. Data were analyzed using the Paired Samples T-Test for numerical scores and Thematic Analysis for interview transcripts. The findings revealed a statistically significant enhancement in oral proficiency; the mean score rose from 62.28 in the pre-test to 77.71 in the post-test, reflecting an average gain of 15.43 points and a percentage increase of 24.77%. Qualitative analysis indicated that the storytelling approach successfully mitigated psychological barriers such as anxiety and low confidence. Consequently, the research concludes that the Storytelling Method is a highly effective pedagogical tool for improving students' speaking skills.